Effects of Antenatal Magnesium Exposure on Intestinal Blood Flow and Outcome in Preterm Neonates - Gursoy, Tugba; Imamoglu, Ebru Yalin; Ovali, Fahri; Karatekin, Guner (American Journal of Perinatology, 2015)
Objective This study aims to investigate the effects of antenatal magnesium sulfate on intestinal blood flow in preterm neonates.Study Design In this prospective case–match study, 25 preterm neonates exposed to magnesium sulfate antenatally were included (study group). Overall, 25 gestational age–matched neonates who had no exposure to magnesium constituted the control group. Serial daily Doppler flow measurements of superior mesenteric artery (SMA) were performed. The time to reach full feeds, first meconium passage were assessed. Presence of feeding intolerance or necrotizing enterocolitis was recorded.Results Blood flow velocities of SMA were not different between the groups during the first five postnatal days. However, SMA blood flow showed an increasing trend in the control group unlike the study group (control group, p < 0.001; study group, p = 0.29). There was no significant difference between the two groups regarding the time to reach full feeds or first meconium passage and presence of feeding intolerance. No case of necrotizing enterocolitis was seen.Conclusion Antenatal magnesium does not significantly affect intestinal blood flow, but it seems to attenuate the increasing trend of the intestinal blood flow in the early postnatal days. However, this study failed to show any impact of this finding on clinical outcomes.
Keywords: blood flow; doppler ultrasound; magnesium; superior mesenteric artery; preterm infant